VIRTUAL SEARCHING OF DUMMY TEMPLATE FOR SINENSETIN BASED ON 2D MOLECULAR SIMILARITY USING CHEMDB TOOL - Iqmal Tahir; Mohd Noor Ahmad; AKM Shafiqul Islam; Dachyar Arbain (Universitas Gadjah Mada, 2012)
Sinensetin-like molecules have been searched virtually to find a dummy template for Molecular Imprinted Polymer (MIP) synthesis. The aim of this study is to find a novel adsorbent for Solid Phase Extraction (SPE) of sinensetin based on tailored method using dummy template. Virtual searching was done using ChemDB online chemical database containing 5 million commercially available chemicals. Sinensetin as target was converted into SMILES code then it was run with threshold of molecular similarity score of 0.5. There were 90 chemical structures given as the output mainly flavone analogue, three flavonols and several non-flavonoid compounds. The suggested results are three dummy templates that derived from luteolin (flavon) or quercetin (flavonol) with slight alteration by methoxylation process.